Cases in Auditing Practice (Book). - Stettler, Howard F.; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "Cases in Auditing Practice," 3rd ed., edited by J. Innes, T.A. Lee and F. Mitchell.